Information Processing and Bounded Rationality: A Survey - Barton L. Lipman (Queen's University, Department of Economics, 1993)
This paper surveys some recent attempts to formulate a plausible and tractable model of bounded rationality. I focus in particular on models which view bounded rationality as stemming from limited information processing. I discuss computability, partitional models (such as automata, perceptrons, and optimal networks), nonpartitional models, and axiomatic approaches
Keywords: 330